Action of Cholesterol-Loaded Cyclodextrin on Viability of Ram Semen - Marques Silva, Juliano Pianowski; Berto de Almada, André Felipe; de Lima, Jonathan Soares; de Freitas Guaitolini, Carlos Renato; Crespilho, André Maciel; Dell´Aqua, Camila de Paula Freitas; Dell´Aqua Junior, José Antônio; de Oliveira Sestari, Danielle Andressa; Dias Maziero, Rosiara Rosaria (Acta Scientiae Veterinariae, 2019)
Background: Studies report that cyclodextrins have the property of carrying cholesterol to the membrane, but in some cases can also remove this cholesterol from the plasma membrane. The mechanism of action of CLC is not well understood, however, it seems to involve sperm protection during the freezing and thawing process. Studies show that its use enhancing increased osmotic tolerance and reduced premature sperm capacitation reaction. In this sense, studies report that cyclodextrins have the property of carrying cholesterol to the membrane, but in some cases can also remove this cholesterol from the plasma membrane. Improvements were reported in the sperm parameters of buffaloes, bulls, stallions and sheep. Ram naturally present less lipids in their membrane, on average 27%, while bulls have 31%, rabbits 62%, and humans 50%. The aimed of the present study was to evaluate the use of cholesterol-loaded cyclodextrin (CLC), a commercial diluent, in the kinetics and viability of frozen and thawed ram spermatozoa. Materials, Methods & Results: Five ejaculates, from five rams of Dorper breed were collected and divided into three groups: control, 1 mg CLC and 2 mg CLC. Semen was diluted in different concentrations of CLC (0, 1, and 2 mg/120×106 spermatozoa), and incubated at room temperature (21°C) for 10 min. Samples were conditioned in 0.5 mL straws and incubated at 5°C for 4 h, exposed to LN2 vapor for 10 min and storing a cryogenic container. The parameters as spermatic kinetics, plasma membrane, acrosomal membrane (MPAI, %), and intracellular levels of superoxide anion (O2-) were evaluated. Sperm progressive motility (PM), rapid spermatozoa percentage (RAP), linearity (LIN, %), average path velocity (VAP, μm/s) and MPAI (%) were more satisfactory with the use of 1 mg compared to 2 mg (P < 0.05). In addition, 1 mg CLC showed decreased levels of superoxide anion formation (O2-), a free radical detrimental to spermatozoa (P < 0.05). The use of 2 mg of CLC reduce VAP (P < 0.05) and did not have any beneficial effect on the evaluated parameters. Discussion: Authors did not observe improvement in the parameters of progressive motility when using 1 mg of CLC in goat semen and 2 mg in bull semen with the slow freezing protocol. This differs from our work, as we found that 1 mg of CLC improved the PM parameters, but not at the concentration of 2 mg CLC. Additionally, authors verified that cyclodextrin at 3 mg concentration was effective in protecting the sperm against the deleterious effects of H2O2. They obtained superior plasma membrane motility, viability, and integrity of the CLC-treated samples compared to the control group. The superoxide anion (O2-) is a free radical formed from molecular oxygen by the addition of an electron. It is generated spontaneously, mainly in the membrane of the mitochondria, by the respiratory chain and by flavoenzimes, lipoxygenases, and cicloxygenases. In our study, we found a difference between the study group with 1 mg CLC and the control group. Thus, we suggest that CLC may have a beneficial effect in stabilizing the sperm plasma membrane. Use of CLC at a concentration of 1 mg was found to be effective for the improvement of parameters of sperm progressive motility, rapid sperm percentage, and plasma and acrosomal membrane integrity. In addition, the study group with 1 mg of CLC showed decreased levels of superoxide anion formation, a free radical detrimental to spermatozoa.